Otimização híbrida por estruturas celulares de rolos de correias transportadoras - Hartmann, Ricardo Augusto Terui (2023)
Conveyor belt systems are responsible for moving bulk materials in several sectors of economy around the world. The correct application and maintenance of these equipment is extremely important to guarantee the continuous operation and supply of the materials they transport. Any downtime can represent a large amount of lost revenue and influence the rest of the supply chain. In this way, the optimized design of these structures with the objective of reducing mass can bring benefits of lower energy consumption for moving the system and easier maintenance and replacement of rolls. Standards from governmental institutes and industrial associations present guides and constructive references for conveyor belts and their components However, there are still some gaps and unexplored situations. The recent advancement of additive manufacturing technology has provided design freedom, previously limited by production processes. Recent studies present the optimization of rolls, a fundamental part of the mechanical functioning of the conveyor belt system. New geometries and materials were suggested. Within this context is inserted the present work, which proposes a hybrid optimization of the design of a polymeric central roll for a carrying idler, considering dimensional parameters of this component (tube and shaft) and the topology by cellular structure (lattice type structure) of the tube. Due to the high computational time required to carry out a direct optimization of the lattice structure, metamodeling based on the Kriging method is used. Which is optimized through the Globalized Bounded Nelder-Mead (GBNM) algorithm and an iterative metamodel refinement process. The optimization problem is defined as the minimization of a combined function of the mass and the compliance of the system, subject to the constraints of the bearing misalignment angle and the allowable stress of the roller tube. Compared to results obtained through parametric optimization, hybrid optimization brought a 10% greater reduction in the roll mass. The mass reduction obtained from this methodology, applied to a constructive type of roller used to transport ore, was 46.3% compared to the initial project.